Improved response-spectrum analysis of base-isolated buildings: A substructure-based response spectrum method. (1st May 2018) - De Domenico, D.; Falsone, G.; Ricciardi, G.
Highlights: New response-spectrum analysis procedure for base-isolated buildings is elaborated. Novel response spectra for base-isolated buildings are constructed. Improvements over the conventional application of the response-spectrum method. The base-isolation system can be modeled as a nonlinear subsystem. Efficiency of the method is demonstrated by comparison with time-history analyses. Abstract: Unsatisfactory numerical predictions may result from applying the classical modal analysis in conjunction with the response-spectrum-method (RSM) to nonclassically-damped systems such as base-isolated buildings. This inaccuracy is highlighted by comparing the conventional RSM outcomes with results from nonlinear time-history analyses consistent with that given spectrum. Indeed, some underlying assumptions of the conventional RSM are not really appropriate for base-isolated buildings, thus only approximate results are obtained, whereas either a complex-value modal analysis or the direct integration of the equations of motion should be undertaken to follow an exact approach to this problem. In an attempt to overcome the limitations of the conventional RSM as well as the mathematical difficulties and computational cost of the exact approach, in this paper an improved response-spectrum analysis procedure for base-isolated buildings is elaborated. Based upon the substructure approach, this procedure makes use of novel response spectra that quantify the effects of the base-isolation-system (BIS) to the superstructure while accounting for the dynamic interaction between BIS and superstructure. The developed procedure improves the conventional RSM in two aspects: (1) the seismic response of the base-isolated building is computed by applying the modal analysis to the superstructure only, which is typically considered as a classically damped system, rather than to the overall structure having nonclassical damping; (2) the BIS can potentially be modeled as a nonlinear subsystem with its actual hysteretic characteristics. The effectiveness of the proposed procedure and the improvements over the conventional RSM are scrutinized against time-history analyses with Monte Carlo simulated spectrum-compatible accelerograms.